“Implementación del Route to Market en la distribuidora Tristar Plus Nestlé de la ciudad de Riobamba, y su incidencia en el crecimiento horizontal de los puntos de venta durante el periodo Junio –Diciembre 2016” - Bravo Mancero, Alicia Catalina (2017)
The research is focused to provide elements that show that the implementation of the Route to Market – RTM in the Tristar Plus Nestlé distributor in Riobamba city, it increases the horizontal growth of points of sale during the period June-December or the year 2016. The poor media coverage through sellers, it has led to limited sales opportunities and therefore inadequate sales development. Thus, the overall objective of the research was to determine the impact of the sales strategy on the growth of the company. The Route to Market is a simple but very powerful methodology to drive profitable growth, while horizontal growth means developing new business within existing structures. From the methodological point of view, it was a descriptive, explanatory, quasi-experimental, field and documentary study. The techniques were used as census and observation with their respective instruments: the census form and the observation sheet. The sample consisted of points of sale for two quarters. The central hypothesis holds that the implementation of Route to Market. It has a significant impact on the horizontal growth of sales outlets. In conclusion, it is established that the implementation of the Route to Market strategy affects the horizontal growth of the points of sale in a direct relation with the increase of sales volume.